2021
DOI: 10.2147/pgpm.s316711
|View full text |Cite
|
Sign up to set email alerts
|

Population Genetic Difference of Pharmacogenomic VIP Variants in the Tibetan Population

Abstract: Background Genetic variation influences drug reaction or adverse prognosis. The purpose of this research was to genotype very important pharmacogenetic (VIP) variants in the Tibetan population. Methods and Materials Blood samples from 200 Tibetans were randomly collected and 59 VIP variants were genotyped, and then compared our data to 26 other populations in the 1000 project to further analyze and identify significant difference. Results The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Usually, SNPs are employed to analyze the pharmacogenomic information in different populations. 3 , 4 “Pharmacogenomics” is an emerging approach to “precision medicine”. Pharmacogenomics plays a major part in precision medicine by “tailoring” the selection and dosing to the patient’s genetic features.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, SNPs are employed to analyze the pharmacogenomic information in different populations. 3 , 4 “Pharmacogenomics” is an emerging approach to “precision medicine”. Pharmacogenomics plays a major part in precision medicine by “tailoring” the selection and dosing to the patient’s genetic features.…”
Section: Introductionmentioning
confidence: 99%
“…They also found that the allele frequency in this Tibetan population differed least from that of an East Asian population, and differed most from that of a North American population. 4 …”
Section: Introductionmentioning
confidence: 99%